Building and rationing the scale of cultural pollution for university students in Baghdad - Abaas, Warda Ali; Kahdum, Saheera Razzak; Abdel-Hussein, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
Pollution is a cultural attack, which in turn brings provisions and laws that are alien and distant from society and in all its fields. The most dangerous field of education is the students and those who are the pillar of society and the basis for drawing out the parameters of its future, through the demolition of cultural values ​ ​ and the denunciation of national privacy. And blindly imitating it which leads to reliability and the inability to take a decision or take responsibility. To prevent this and to preserve cultural privacy and preserve it as an asset to enrich Iraqi human civilization, the problem of research in studying cultural pollution came to identify its level among university students. Standard dimensions and the total score of a measure of cultural pollution for university students, and the identification of the level of dimensions and the general total of cultural pollution among students of physical education and sports science / Baghdad. The researchers chose the descriptive analytical approach to its suitability of the research problem. The research community was chosen from university students in Baghdad (Baghdad, Al-Mustansiriyah) and their number was (1029) students for the academic year (2016-2017). They were divided into three groups, the first group is the construction sample (240 students) Male and female students, and the second group, the rationing sample (240), and the third group (649), for measurement. After collecting the data, the results were extracted and the most important conclusions were reached: The cultural pollution scale is valid for university students (male and female). Standardization (finding standard levels) for the dimensions and overall degree of cultural pollution. The level of cultural pollution among students of physical education and sports science was small. The most effective dimensions of cultural pollution among students of physical education and sports science were because of the ideas and the least of them after the appearance.